(3agQSJs - (3GdcJGfj , eMeO Hf YHO GdcHjQ Hf eMeO, CHh GdajV CHh YHO Gddg,J (B1327 (3g` s
(3ChdgG (B:s
(3ef NGOe fYGd GdeMOKjf eMeO Hf GdMi Hf TjNI GdTjN YHO GdcHjQ GdcJGfi Edi CNjg ehdGfG eMeO Hf CMeO GdMSfi CeG HYO , abO hUdfG cJGHce GdCRgQ s
(3BNQgG (B:s
(3aEf dPG PGJ GdeTGgO Sehe GdefGjG ai cDhS GdeVGjb s
(3Vef eLehY , JQJjHgG (B: (3ef U (B1 - (3U(B144s
(3hbO PcQ ajg CSGfjOg hTjhNg hELGRGJgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B214 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B185s
(3Odjd eDQN GdeZQH (B- (3U (B366 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B317 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3GdJGQjNs